Description Of The Characteristics Of Patients With Presbycusis At Tangerang City Hospital For The Period 2014-October 2023 - Syukrinto, Gustav; Lucyana Achwas; Hendrarto, Hendrarto; Aris Mahfuzhi (Al Makki Publisher, 2023)
Presbycusis has a prevalence of 30-45% in the elderly aged older than 65 years, especially in men. In Indonesia, 30-35% of the elderly aged 65-75 years experience presbycusis. This study aims to determine the prevalence of presbycusis cases in the ENT-BKL Poly of Tangerang City Hospital for the period 2014-October 2023. This study is a crossectional descriptive study conducted from November to December 2023 at RSUD Kota Tangerang, with inclusion criteria for age ≥ 65 years old from down slooping audiometry. The results of this study data found 48 cases of presbycusis obtained by 35 patients (72.92%), women as many as 13 patients (27.08%). Based on the guarantee, it was found that BPJS users were 43 patients (89.58%), general financing was 5 (10.42%) patients. Of the total 48 cases of presbycusis 10 (20.83%) patients received hearing aid therapy and 38 (79.17%) other patients were non-hearing aids.